The burden of obesity in the current world and the new treatments available: focus on liraglutide 3.0 mg - Mancini, Marcio C. (Diabetol Metab Syndr, 2017)
The prevalence of obesity increases worldwide. Treating obesity and its associated health problems has a significant economic impact on health care systems. The unsatisfactory long-term outcomes observed in the obesity treatment are due to its complex pathophysiology and the inherent difficulties associated with maintenance of lifestyle modifications. Determined by genetic and environmental factors, obesity has been officially recognized as a chronic disease, an action that allowed the recognition of anti-obesity drugs as legitimate therapeutic options to address the growing obesity endemic. Like other chronic diseases, obesity requires long-term treatment. Pharmacological interventions, when used as an adjunct to lifestyle changes, are useful to facilitate clinically meaningful weight loss, which may impact on obesity-associated comorbid conditions. In the past, medications for weight reduction were limited. However, the landscape has changed and new drugs provide additional options for weight management. Among the new drugs, liraglutide is the most studied, especially regarding its effects on the limbic system. As an adjunct to a reduced-calorie diet and increased physical activity, treatment with liraglutide 3.0 mg provides a statistically significant and clinically meaningful weight loss. Liraglutide is a glucagon-like peptide 1 (GLP-1) receptor agonist that shares 97% homology to native GLP-1. Receptor agonists of GLP-1, including liraglutide, have emerged as effective therapies for type 2 diabetes and obesity. This review will address the major findings concerning the central regulation of appetite and the main studies that evaluated new drugs for obesity treatment, with a greater focus on liraglutide 3.0 mg.